Groundwater quality in the jaffna peninsula of sri lanka and a qualitative study of btex removal by greenly synthesized iron nanoparticles-electro-catalyst system - Ehanathan, S.; Raagulan, K.; Rajapakse, R.M.G.; Velauthamurty, K. (University of Jaffna, 2020)
The Jaffna peninsulais northern part of Sri lanka (Longitude: 80 060 2.2800 E and Latitude: 9 410 12.2000 N), mainly gains water from groundwater which is continuously protected by various human activity even with reckless deterioration. The maximum nitrate concentration reached up to 51 ppm whereas the amount of phosphate found to be as 3.8 ppm. The average EC for a year is 38.1 mS/cm and corresponding salinity and TDS found to be as 20.2 and 24.3 g/L respectively. The middle region of the territory consists less saline water and 0.132 ppm of Pb and 0.092 ppm Cd presence in the groundwater. The BTEX has been completely eradicated by using the cost-effective environmentally-friendly electrochemical system. The developed system can be utilized the application areas such as service station, mechanic stores, hospitals, universities and household purpose.
Keywords: BTEX; Iron nanoparticle; TDS; EC; Heavy metals